Do texto literário ao jogo - Araujo, Maria Ivania dos Santos (2018)
One of the concerns of society and professionals in the field of education is the work with reading and, consequently, the critical formation of the reader. This is justified, above all, by a literacy policy that aims to improve learning in reading and interpreting texts. In addition, as teachers of Portuguese language in public schools, we also think about the need to train literary readers. Yet the meager resources and limited form as the literary text is presented in the textbook become part of the challenge of literary reading practices. Given this scenario, there is a need for professionals in the area of Literature to undertake studies on this subject and promote actions that allow for a change. Thus, we propose the performance of a work in which the fairy tales rescue the literary text in its multifaces, starting from the reading and returning to it, so that one of the functions of the literary text is used - the hedonistic one. Pleasure occurs in two ways: the enjoyment with the readings and the game "Contigos". In carrying out this work he also focused on instruction, self-knowledge, coming from these texts. We seek the views of the theorists Rildo Cosson (2006), Bruno Bettelheim (2008), Geraldi (2008), Nelly Novaes Coelho (2003), Jesualdo (1993), Huizinga (2008) among others for bibliographical references. As a result of this work, a methodology of teaching the literary text through fairy tales and a game, in order to broaden the debate about the improvement in the teaching of literary reading in classrooms, so that there is a strengthening of literary literacy in Elementary School II.